2009
DOI: 10.1159/000218350
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Interstitial High-Dose-Rate Brachytherapy in Hepatocellular Carcinoma

Abstract: New interventional options especially for patients with HCC and BCLC scores B and C give rise to disputes about the optimal therapeutic management. CT-guided brachytherapy complements established interventional techniques like RFA and TACE since it may also be used successfully in tumors much greater than 5 cm in diameter. In addition, unlike thermal ablation, the brachytherapy technique may be applied in tumors located nearby risk structures such as liver hilum or gallbladder and it is independent of cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Ricke and colleagues, who first studied this technique, have reported equally satisfactory results in preceding studies [10]. In a pilot study, Mohnike et al reported local tumour control (93% after 12 months) and progression-free survival (6 months in 79% of patients and 12 months in 54%) comparable to those in the present study [39,40]. In a follow-up trial including 83 patients with 140 lesions treated with CT-HDRBT and a matched-pair analysis with a historical control group, Mohnike et al demonstrated a high positive impact of CT-HDRBT on overall survival as compared with standard treatments including TACE and RFA [10].…”
Section: Discussionsupporting
confidence: 82%
“…Ricke and colleagues, who first studied this technique, have reported equally satisfactory results in preceding studies [10]. In a pilot study, Mohnike et al reported local tumour control (93% after 12 months) and progression-free survival (6 months in 79% of patients and 12 months in 54%) comparable to those in the present study [39,40]. In a follow-up trial including 83 patients with 140 lesions treated with CT-HDRBT and a matched-pair analysis with a historical control group, Mohnike et al demonstrated a high positive impact of CT-HDRBT on overall survival as compared with standard treatments including TACE and RFA [10].…”
Section: Discussionsupporting
confidence: 82%
“…Brachytherapy under CT control has been described as a safe and effective method for the treatment of primary and secondary liver lesions (13,(16)(17). In the present study, brachytherapy under CT as a palliative method of treating liver metastases was demonstrated to be an effective and safe method for the patient and a technically feasible procedure.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, Mohnikeet al [32] was able to demonstrate a significant improvement of survival in patients with versus cases without BT of locally advanced HCC manifestation.…”
Section: Resultsmentioning
confidence: 90%
“…In particular, for pulmonary and hepatic metastases of colorectal carcinomas and for hepatocellular carcinoma (HCC), effectiveness by radiotherapy modes has been detected with regard to local tumor control and overall tumor prognosis [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%